A Lectin AtTL-2 Obtained from Acropora aff. tenuis Induced Stimualation of Phagocytosis of Symbiodiniaceae - Mitsuru Jimbo; Nami Kuniya; Yuna Fujimaki; Daiki Yoshikawa; Naoki Kamiya; Haruna Amano; Ko Yasumoto; Ikuko Yuyama; Go Suzuki; Saki Harii (Microorganisms)
The coral Acropora aff. tenuis selectively acquired various zooxanthella (Symbiodiniaceae) strains, and one of the selective factors was lectins. The A. aff. tenuis lectin AtTL-2 was identified as a factor for Symbiodiniaceae acquisition by the coral, but the mechanism is not fully known. The acquisition process involves three steps: chemotaxis, entry into the coral, and phagocytosis. In this study, we examined the function of AtTL-2 in more detail. Immunohistochemistry analysis was performed to examine the distribution of AtTL-2. The effect of AtTL-2 on the number of Symbiodiniaceae acquired was measured in A. aff. tenuis juvenile polyps with and without AtTL-2 siRNA treatment. The effect of AtTL-2 fixation was examined by monitoring the acquisition of AtTL-2–fixed beads by A. aff. tenuis. AtTL-2 was distributed in nematocysts, spirocysts, and around Symbiodiniaceae. AtTL-2 siRNA inhibited the acquisition of Symbiodiniaceae by juvenile polyps. Fixation of AtTL-2 promoted bead acquisition by juvenile polyps more than fixation of bovine serum albumin (BSA). Moreover, more AtTL-2–fixed beads were bound to the Symbiodiniaceae-enclosed cells than BSA-fixed beads. AtTL-2 is released from spirocysts and binds to Symbiodiniaceae. AtTL-2 then promotes the phagocytosis of Symbiodiniaceae by gastrodermal cells of A. aff. tenuis.